Revisiting Thompson’s Multicultural Disposition Index in preservice English teacher education in Indonesia - Lusi Nurhayati; Suwarsih Madya; Nur Hidayanto Pancoro Setyo Putro; Sulis Triyono (Studies in English Language and Education, 2022)
Despite the growing body of literature recognizing the importance of multicultural education in the 21st Century, little is known about the preservice English teachers’ (PSETs) multicultural disposition (MD) in the Indonesian setting. This survey study examined the Multicultural Dispositions Index (MDI) of PSETs. The 22 items of Thompson’s (2009a) MDI scales with four dimensions, i.e., cross-cultural competence, multicultural worldview, knowledge of professional and personal self, and professional skills and commitment, were adopted to explore the PSET MDI in this study. It was a nine-type self-report scale. The study involved 185 PSETs (aged 17–22 years; 146 females and 39 males) from one of well-established teacher education universities in Indonesia. A Confirmatory Factor Analysis was conducted to confirm the underlying MDI dimensions. The findings showed that the PSETs MDI was best represented by 18 items that emerged into the same four dimensions. It means the PSETs in Indonesia possess the four dimensions of multicultural dispositions, facilitating them to navigate school-level multicultural education. Four items from the original 22 items of MDI must be due to the cross-loading and low factor loading since the value was found to be more than 0.50. Therefore, it is strongly recommended that the MDI be revised when used in the Indonesian multicultural context.